Effect of feeding fat on fibrinolysis, stypven time, and platelet aggregation in elderly Africans. Issue 7 (July 1972) - Ferguson, J. C.; Mackay, N.; McNicol, G. P.
Abstract : The effects of acute fat feeding on fibrinolytic activity, platelet aggregation, and stypven time in six elderly Africans are presented. These indicate that there is no alteration in the pattern of response seen in Africans with advancing age.